Determining the optimum high-flow nasal cannula flow rate to achieve the desired fraction of inspired oxygen: A bench study - Chao-Lan Huang; Chun-Ching Lu; Cheng Chiang; Heng-Sheng Chao; Ting-Yun Chiang; Wei-Nung Teng; Wen-Kuei Chang; Chien-Kun Ting (Journal of the Formosan Medical Association)
Background: Purpose: High-flow nasal cannula (HFNC) has many benefits in various clinical conditions. The original hypothesis suggests that the high and constant fraction of inspired oxygen (FiO2) is one of the main physiological effects. However, increasing evidence shows that there is a gap between the actual FiO2 and administered FiO2. We aimed to determine the actual FiO2 under different respiratory conditions and develop a regression model using a spontaneous breathing lung model. Methods: A spontaneous breathing simulation model was built using an airway manikin and a model lung. The FiO2 was measured under different respiratory conditions with varying tidal volumes and respiratory and HFNC flow rates. The relationships between the respiratory parameters and actual FiO2 were determined and used to build the predictive model. Results: The actual FiO2 was negatively correlated with respiratory rate and tidal volume and positively correlated with HFNC flow. The regression model could not be developed using simple respiratory parameters. Therefore, we introduced a new variable, defined as flow ratio, which equaled the HFNC flow divided by inspiratory flow. Our equation demonstrated that the actual FiO2 was mainly determined by the flow ratio in a non-linear relationship. Accordingly, a flow ratio greater than 1 did not ensure a constant high FiO2, whereas a flow ratio >1.435 could produce FiO2 >0.9. Conclusion: The FiO2 during HFNC was not constant even at sufficiently high oxygen flow compared with inspiratory flow. The predictive model showed that the actual FiO2 was mainly determined by the flow ratio.